Sociolinguistic and Phonetic Perception of Second Language Mandarin Chinese - Squizzero, Robert L (My University, 2022)
Perception of second language (L2) speakers and their speech is known to be influenced both by phonetic and by sociolinguistic factors. The existing body of scholarly research on L2 speech perception, however, is overwhelmingly focused on Indo-European languages, raising doubts about the generalizability of existing sociolinguistic, phonetic, acquisition, and pedagogical theory to other linguistic contexts. This dissertation aims to work towards rectifying this problem through a series of related studies investigating factors affecting the perception of L2 Mandarin Chinese. Chapters 1 and 2 consist of a group of closely related studies investigating the effect of perceived ethnicity on perception of language proficiency - including accentedness - and of speaker personal characteristics. Chapter 1 contains the first known study to establish that there is an effect of perceived ethnicity on perception of personal characteristics of L2 speakers of a non-Indo-European language. Chapter 2 confirms the results of Chapter 1 with a larger and more diverse sample, allowing for an investigation of differences between listeners that may affect perception of speakers. The excursus to Chapter 2 expands on the findings of the main study by providing evidence for mediating and moderating factors of gendered and racialized judgments of L2 Mandarin speakers. Chapter 3 is a phonetic production study of L2 Mandarin consonants and vowels under the influence of L1 English, with careful attention paid to English and Mandarin dialectal variation. In a study analyzing the time-varying properties of vowels using generalized additive mixed models, Chapter 3 demonstrates that five phonemic vowels significantly differ between first language Mandarin speakers and advanced and intermediate L2 Mandarin speakers. Chapter 4 uses speech analyzed in Chapter 3, the procedures used in Chapters 1 and 2, and additional procedures from the intelligibility-comprehensibility-accentedness literature to establish sociolinguistic and phonetic factors interact to influence perception of adult L2 Mandarin Chinese. Together, these studies demonstrate that both beliefs about a speaker’s perceived social group membership and the acoustic properties of speech indeed affect intelligibility, comprehensibility, accentedness, and perceived personal characteristics of L2 Mandarin Chinese speakers.
Thesis (Ph.D.)--University of Washington, 2022
Keywords: Chinese; Mandarin; Phonetics; Second Language Acquisition; Social psychology; Sociolinguistics; Linguistics; Sociolinguistics; Psychology; Linguistics